2019
DOI: 10.3390/molecules24112182
|View full text |Cite
|
Sign up to set email alerts
|

Lycopodium Attenuates Loss of Dopaminergic Neurons by Suppressing Oxidative Stress and Neuroinflammation in a Rat Model of Parkinson’s Disease

Abstract: Parkinson’s disease, a chronic, age related neurodegenerative disorder, is characterized by a progressive loss of nigrostriatal dopaminergic neurons. Several studies have proven that the activation of glial cells, presence of alpha-synuclein aggregates, and oxidative stress, fuels neurodegeneration, and currently there is no definitive treatment for PD. In this study, a rotenone-induced rat model of PD was used to understand the neuroprotective potential of Lycopodium (Lyc), a commonly-used potent herbal medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 70 publications
5
19
1
Order By: Relevance
“…H&E staining revealed degenerative and necrotic changes in the form of shrunken neurons with dark cytoplasm and pyknotic nuclei. The neurodegeneration was reflected by the loss of TH-positive cells in the SN region, which is in line with previous studies [41,42]. The administration of pomegranate juice to rotenone-intoxicated rats ameliorated the damaging effect of the neurotoxin since only some neurons with dark cytoplasm were still observed in the SN region and enhanced survival of TH+ neurons in this area was noticed.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…H&E staining revealed degenerative and necrotic changes in the form of shrunken neurons with dark cytoplasm and pyknotic nuclei. The neurodegeneration was reflected by the loss of TH-positive cells in the SN region, which is in line with previous studies [41,42]. The administration of pomegranate juice to rotenone-intoxicated rats ameliorated the damaging effect of the neurotoxin since only some neurons with dark cytoplasm were still observed in the SN region and enhanced survival of TH+ neurons in this area was noticed.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we assessed the effects of pomegranate juice treatment on the antioxidant defense system in the midbrain. Although many authors have shown the decrease in GSH level and/or antioxidant enzymes activity in this brain area of rats exposed to rotenone [31,[40][41][42][47][48][49][50], in our experiment, these markers were not affected significantly by rotenone administration. Differences in the response can be associated with the higher doses of rotenone, ranging between 1.5 mg/kg b.w.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations